Impact of the Integrated Care Model in improving health care seeking behaviours in Mashonaland East, Zimbabwe - Mhlanga, Maxwell; Midion, Chidzonga; Clara, Haruzivishe (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
BACKGROUND OR OBJECTIVES: Poor access and utilisation of health care services remains a big challenge in rural communities in low to middle income countries leading to high prevalence of preventable childhood illnesses and death. There is a dearth of qualitative information to explain the poor health care seeking practices by caregivers in Zimbabwe. The purpose of this study was to examine the usefulness of the Integrated Care Model in predicting and promoting positive behaviour change in Mashonaland East, Zimbabwe. METHODS: This was a qualitative study that employed an interpretive case study approach at 2 health centres in Zimbabwe. Twelve audiotaped in-depth interviews with care-givers, community health worker and healthcare professionals were conducted from the catchment area for the two health centres. Descriptive statistics were used for the sample demographics. Transcripts were analysed through thematic analysis. RESULTS: The mean age of the participants was 32 years (SD=3.4). In this study, poverty, gender inequality and negative norms, cultural practices and religious practices were reported to be the major barriers to uptake of maternal and child health services. The perceived benefits of the Integrated Care Model included increasing the knowledge on maternal and child health, increasing uptake of recommended maternal and child health practices and improving maternal and child health outcomes. The participants recommended continual supportive visits, promotion of recommended practices through small awards to the positive deviant households and recognition of the work of community volunteers. Integration of education sessions with income generating activities was proposed to promote high retention rates in the learning groups. CONCLUSION The Integrated Care Model is an effective model that has potential to improve maternal and child health outcomes in low resource settings. Countries in low resource setting can improve their child health outcomes through this low-cost high impact initiative.